Hypertensive emergency preceding the progression of periaortitis and retroperitoneal fibrosis: case report and review of the literature. (2nd September 2016) - Ito, Takayasu; Okamoto, Ryuji; Taniguchi, Masaya; Tanabe, Masaki; Komatsubara, Haruna; Yamada, Norikazu; Ito, Masaaki
Abstract: Hypertensive emergency is an important entity which should be managed adequately. A 65-year-old woman presented with blindness and elevated blood pressure of 254/131 mmHg. She was diagnosed with hypertensive emergency on physical examination, and brain magnetic resonance imaging showed posterior reversible encephalopathy syndrome (PRES) with bilateral thalamic haemorrhage. After controlling her blood pressure with intravenous antihypertensive agents, periaortitis and retroperitoneal fibrosis (RPF) were manifested by left hydronephrosis and creatinine elevation. She was diagnosed with periaortitis/RPF. Her blood pressure was well controllable, and PRES improved after treatment with prednisolone. Periaortitis/RPF should not be overlooked when hypertensive emergency suddenly occurs in patients with no history of hypertension.